2018
DOI: 10.1093/infdis/jiy182
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Analysis of Reemerging GII.P16-GII.2 Noroviruses in 2016–2017 in China

Abstract: Our findings provide new insights into GII.2 norovirus epidemics and highlight the necessity of enhanced global surveillance for potential epidemics of rare-genotype noroviruses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
60
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 52 publications
(70 citation statements)
references
References 36 publications
10
60
0
Order By: Relevance
“…The first GII.2[P16]positive sample was detected in August 2016 in Guangdong Province (36,37), and the number subsequently increased, with GII.2[P16] accounting for 70%-100% of norovirus outbreaks during winter 2016-17 in different provinces (38)(39)(40). Previous studies suggested that reemerging GII.2[P16] virus most likely evolved from strains emerging during 2012-2013 (41). Although the antigenicity and histo-blood group antigen binding profile of the early 2016-2017 and pre-2016 GII.2 noroviruses were similar, 1 GII.2[P16] strain with single Val256Ile mutation and the conventionally orientated Asp382 in VP1 showed an expanded histo-blood group antigen binding spectrum in China (41).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The first GII.2[P16]positive sample was detected in August 2016 in Guangdong Province (36,37), and the number subsequently increased, with GII.2[P16] accounting for 70%-100% of norovirus outbreaks during winter 2016-17 in different provinces (38)(39)(40). Previous studies suggested that reemerging GII.2[P16] virus most likely evolved from strains emerging during 2012-2013 (41). Although the antigenicity and histo-blood group antigen binding profile of the early 2016-2017 and pre-2016 GII.2 noroviruses were similar, 1 GII.2[P16] strain with single Val256Ile mutation and the conventionally orientated Asp382 in VP1 showed an expanded histo-blood group antigen binding spectrum in China (41).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies suggested that reemerging GII.2[P16] virus most likely evolved from strains emerging during 2012-2013 (41). Although the antigenicity and histo-blood group antigen binding profile of the early 2016-2017 and pre-2016 GII.2 noroviruses were similar, 1 GII.2[P16] strain with single Val256Ile mutation and the conventionally orientated Asp382 in VP1 showed an expanded histo-blood group antigen binding spectrum in China (41). Unlike previously emergent GII.4 viruses, GII.2[P16] did not become a globally predominant genotype; however, this emerging virus was also detected in other countries, such as Germany, Italy, Japan, France, and the United States (42)(43)(44).…”
Section: Discussionmentioning
confidence: 99%
“…Genetic recombination frequently occurs in RNA viruses and, since the first description of a naturally occurring norovirus recombination in 1997 [54], recombinant norovirus have been reported worldwide, including the region of Valencia [55]. Different studies have revealed an emergence of GII.P16-GII.2 recombinant strain in 2016 in different parts of the world [56][57][58][59]. This recombinant strain could become the currently predominant variant and be responsible for upcoming outbreaks of acute gastroenteritis caused by noroviruses.…”
Section: Discussionmentioning
confidence: 99%
“…It is noteworthy that, in addition to GII.4, a novel variant of GII.17 and a recombinant variant of GII.2 (GII. P16/GII.2) had a wide distribution between 2014 and 2015 and 2016 -2017, respectively [38][39][40][41].…”
Section: Genotype Diversitymentioning
confidence: 99%